1979
DOI: 10.1021/bi00589a021
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleic acid synthesis in isolated Drosophila nuclei

Abstract: We have developed a system for studying transcription in nuclei isolated from Drosophila melanogaster tissue culture cells. These nuclei synthesize RNA at the rate of 75-100 pmol/pg of DNA in 30 min. About 20% of the RNA synthesized is released from the nuclei, and both released and nonreleased RNAs have poly(A) on them. By use of mercury-agarose affinity chromatography and 5'-[y-SIGTP or 5'-[y-S]ATP precursors as an assay for initiation, it has been determined that approximately 16% of the radioacivity incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In both of these systems bovine serum albumin had no significant effect on the early stages of RNA synthesis, but rather enhanced the long-term stability of the RNA (9) or resulted in increased total synthesis (7). We found that the addition of bovine serum albumin to levels comparable to those used in the studies described above (8,10) had no affect on apparent degradation (data not shown).…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…In both of these systems bovine serum albumin had no significant effect on the early stages of RNA synthesis, but rather enhanced the long-term stability of the RNA (9) or resulted in increased total synthesis (7). We found that the addition of bovine serum albumin to levels comparable to those used in the studies described above (8,10) had no affect on apparent degradation (data not shown).…”
Section: Resultsmentioning
confidence: 77%
“…4; in this experiment the KCl concentration was 100 mM, and the MgCl2 concentration was varied from 0.5 to 40 mM. Total incorporation was maximal between 10 and 20 mM MgCl2; higher levels of MgCl2 result in decreased total incorporation, but the percentage of a-amanitin- sensitive activity increased (data not shown). When individual transcripts were analyzed by hybridization (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations